Knowledge, Attitude and Perception Toward COVID-19 Vaccine among the General People - Paudel , Pramod; Sapkota, Shubha Devi; Subedi, Jyoti (Journal of Bharatpur Hospital, 2025)
Background The most effective method of controlling the spread of the SARS-CoV-2 virus is to protect oneself from exposure and immunize against it, a public health priority. This study aimed to identify knowledge, attitudes, and perceptions regarding the COVID-19 vaccine in Nepal. Methods A cross-sectional descriptive web-based study was conducted among 449 adults aged 18 to 40 years in August 2021. A Google form survey was used which included 18 structured questions, where an overall greater score denotes positive knowledge, attitude, and perception toward COVID-19 vaccination. Data were analyzed using SPSS. Results Out of 449 respondents, two-thirds were female, with a mean age of 20.71 years (SD = 2.98). The mean knowledge score regarding COVID-19 vaccination was 2.96 (SD = 1.16), while the mean attitude score was 15.93 (SD = 2.08). Overall, 84.2% of participants agreed that vaccines are essential to them, and 90.2% reported encouraging their family members to receive the COVID-19 vaccine. Additionally, 86.2% believed that the vaccine could have side effects, and 54.3% thought that preventive measures could eliminate the need for vaccination. Conclusions The study concluded that the general population possesses an average level of knowledge and females had a better attitude towards vaccine and were generally supportive of it. Most people continued to worry about the vaccine’s adverse effects. Continued community education regarding the COVID-19 vaccine and its benefits should be conducted.